Incidence of Cardiogenic Shock Among Acute STEMI Cardiac Patients - Zia Ullah, Aman Ullah, Mujeeb Alam Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Coronary Artery disease is a serious health issue affecting both men and women thus becoming the leading cause of death globally. Aims: To determine the frequency of cardiogenic shock in patients with acute ST elevation myocardial infarction. Study Design: Cross-sectional comparative study. Methodology: All newly diagnosed acute ST elevation MI patients were included. Detailed history followed by detailed clinical examination was done. ECG and urinary output were measured to detect ICS. All this information was recorded on Performa. Statistical analysis: Data was analyzed using SPSS version 25. Cardiogenic shock was stratified among age and gender by applying chi square test. Results: Age as mean ± SD was 60 ± 1.26 years. Males were 68% while females were 32% enrolled in present study. Results showed that only 10% patients had cardiogenic shock while 90% were without it. Conclusion: It was concluded that the frequency of cardiogenic shock was low (10%) in patients with acute ST elevation myocardial infarction.